Impact of Built Shape, Forms and Spaces on Human Psychology - Shourya Jain; Shashi Saxena; Ankita Srivastava (International Journal of Architectural Design and Planning, 2024)
Shelter is the essential component for human survival, yet they know more about the effects of environmental conditions on human health than they know about how a building’s geometry affects the human brain. Typically, architects work on geometry to integrate the appearance of structures, but design-oriented geometry ignores human experience with respect to psychology and emotion. The psychological effects of architectural geometry on human senses, behaviors, and experiences are the main topic of this paper. Shapes and forms can convey a wide range of emotions and feelings, from harmony and balance to tension and discomfort, and they can be used to express complex ideas and concepts. In order to comprehend how they should design and what they should be concerned about throughout design, it is essential and vital to combine the senses, emotions, and experiences with conventional architectural design theories and methodologies.
Keywords: Architecture; form; psychology; shape; space